2017
DOI: 10.1155/2017/2981071
|View full text |Cite
|
Sign up to set email alerts
|

Transient Free Convective MHD Flow Past an Exponentially Accelerated Vertical Porous Plate with Variable Temperature through a Porous Medium

Abstract: This paper is concerned with analytical solution of one-dimensional unsteady laminar boundary layer MHD flow of a viscous incompressible fluid past an exponentially accelerated infinite vertical plate in presence of transverse magnetic field. The vertical plate and the medium of flow are considered to be porous. The fluid is assumed to be optically thin and the magnetic Reynolds number is considered small enough to neglect the induced hydromagnetic effects. The governing boundary layer equations are first conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 13 publications
6
23
0
Order By: Relevance
“…The results are illustrated graphically through MATLAB, and the variation of skin friction, Nusselt number, and Sherwood number with multiple values of the suitable parameters are exhibited through tables. Besides, a comparison of the existing results with that of the previous author Paul 27 was made in Figure 20, and they are in good agreement.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The results are illustrated graphically through MATLAB, and the variation of skin friction, Nusselt number, and Sherwood number with multiple values of the suitable parameters are exhibited through tables. Besides, a comparison of the existing results with that of the previous author Paul 27 was made in Figure 20, and they are in good agreement.…”
Section: Introductionsupporting
confidence: 67%
“…Fluid suction is a technique by which separation of the boundary layer can be prevented while maintaining the laminar nature of the flow. The combination of fluid suction or fluid injection with heat transfer makes the study more intriguing studied by Ahmed et al, 23 Jha et al, 24 Parida et al, 25 and Ajibade et al 26 Paul 27 has used the Laplace transform technique to obtain an exact analytical solution of MHD flow, depending on time, with fluid suction influenced by thermal radiation. The analysis revealed that radiation or suction enhanced the heat transfer rate near the plate surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of their mathematical model was Finite Element Method. The MHD free convection was noted under different temperatures by Paul [5] on an exponentially accelerated porous plate. Laplace transform technique was used by him.…”
Section: Introductionmentioning
confidence: 99%
“…Rajput and Gaurav Kumar 12 analysed hall current effects on unsteady magneto hydro dynamic flow past an impulsively started inclined oscillating plate with variable temperature and mass diffusion . Ashish Paul 13 gave analytical solution of one-dimensional unsteady laminar boundary layer MHD flow of a viscous incompressible fluid past an exponentially accelerated infinite vertical porous plate in presence of transverse magnetic field. Prema and Muthucumaraswamy 14 examined the effects of the thermal radiation effects on unsteady free convective flow of a viscous incompressible flow past an exponentially accelerated infinite vertical plate with variable temperature and mass diffusion By influencing the above studies we analysed the effect of Radiation parameter on unsteady free convection flow of an electrically conducting fluid past an exponentially accelerated infinite vertical plate with constant heat flux through a porous medium under the influence of uniform magnetic field fixed to the fluid or to the plate in the presence of chemical reaction and heat absorption.…”
Section: Introductionmentioning
confidence: 99%